PROMOSI KESEHATAN GIGI DAN MULUT BERBASIS PENDIDIKAN ISLAM SEBAGAI UPAYA PENCEGAHAN KARIES PADA ANAK USIA SEKOLAH SDN BALANG BODDONG MAKASSAR - Muhammad Jayadi Abdi; Andi Azisa Dyah Septiriani; Andini Dyvani Pratiwi (BESIRU : Jurnal Pengabdian Masyarakat, 2026)
Dental caries is one of the most common health problems found in school-aged children. Promotive and preventive efforts are needed to prevent caries, one of which is through dental and oral health promotion. This community service activity aims to improve knowledge, attitudes, and behaviors regarding dental and oral health based on Islamic education among fourth-grade students of SDN Balang Boddong. The research method used a quantitative approach with a cross-sectional design. Data collection was conducted by distributing questionnaires to 35 respondents. The results showed that the majority of respondents had a good level of knowledge (86%), positive attitudes (54%), and good behavior (60%). The conclusion of this community service activity is that a health promotion approach based on Islamic education has the potential to increase understanding and support changes in behavior regarding dental and oral health maintenance.